2010
DOI: 10.1080/15435075.2010.502040
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Recovery of Benthic Macroinvertebrate Communities in Junction Creek, Sudbury, Ontario, after the Diversion of Acid Mine Drainage

Abstract: Restoration of streams impacted by acid mine drainage (AMD) often require extensive and expensive engineering solutions, but the long-term effectiveness of these treatments in terms of improving downstream biological communities, is rarely tested. A rather novel treatment for the elimination of AMD at a site on Junction Creek in Sudbury Canada, involved damming and diversion of AMD deep underground, with subsequent limestone treatment of the waters outside the watershed. We used a rapid bioassessment technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Local macroinvertebrate taxonomic richness, mean macroinvertebrate density, mean live biomass, and Shannon Wiener diversity index were all significantly higher in 2011 (post-restoration) than in 1967 (pre-restoration), and regional taxonomic richness throughout the watershed more than doubled after remediation efforts were implemented. These results are consistent with studies showing that degradation of water quality from AMD is typically associated with a reduction in the diversity and abundance of macroinvertebrates (Tomkiewicz and Dunson, 1977;Kimmel, 1983), and studies demonstrating biological recovery from AMD following restoration (Nelson and Roline, 1996;Gunn et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…Local macroinvertebrate taxonomic richness, mean macroinvertebrate density, mean live biomass, and Shannon Wiener diversity index were all significantly higher in 2011 (post-restoration) than in 1967 (pre-restoration), and regional taxonomic richness throughout the watershed more than doubled after remediation efforts were implemented. These results are consistent with studies showing that degradation of water quality from AMD is typically associated with a reduction in the diversity and abundance of macroinvertebrates (Tomkiewicz and Dunson, 1977;Kimmel, 1983), and studies demonstrating biological recovery from AMD following restoration (Nelson and Roline, 1996;Gunn et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…Despite rehabilitation actions and improved physico-chemical properties, Junction Creek shows similar responses to what was observed in surrounding lakes where signs of biological perturbations are still present. For example, a study on macroinvertebrate assemblages from 2000 to 2008 suggests slow recovery in Junction Creek (Frood Branch) after diversion of acid mine drainage in 2000, when many large sensitive invertebrates were still lacking [2]. Although metal contamination has drastically been reduced in the region, Weber et al (2008) also showed biological impacts with increasing metal concentrations (Cd, Cu, Rb, Se, and Sr) in fathead minnow and creek chub along a downstream gradient in Junction Creek.…”
Section: A Brief History Of Mining Around Sudbury and The Resulting Ementioning
confidence: 99%
“…The health of Junction Creek was impacted by the contamination and degradation in its watershed, and showed highly impaired biological integrity [1]. Still nowadays, despite pollution control and rehabilitation actions having been undertaken, aquatic ecosystems in the region suggest slow recovery [2][3][4][5][6]. Mining activities are still present in the region, although under significantly more restrictive pollution control and regulation, and intensification of urban development represents a supplementary environmental threat.…”
Section: Introductionmentioning
confidence: 99%
“…Three of those reported impacts that clearly show negative and long-lasting effects on invertebrate communities, especially reduced diversity, when receiving waters and sediments contain bioavailable metals. Recent studies in metal-contaminated lakes or streams continue to show lower invertebrate diversity than in uncontaminated systems, although some trends of recovery are evident where effluents or emissions have been reduced (Gunn et al 2010;Wesolek et al 2010). By contrast, Spencer et al (2008) found evidence of eutrophication and resultant increased invertebrate abundance and diversity downstream of metal mines.…”
Section: Macroinvertebratesmentioning
confidence: 99%